Marketization as a context for crime: the scandals in further education colleges in England and Wales - Denham, David (Crime, law and social change, 2002)
The paper outlines the marketization of further education in England and Wales in 1993 and the scandals which followed these market reforms. The case study supports theories that predict market societies provide a cultural and structural context for crime.